2022
DOI: 10.1093/braincomms/fcac179
|View full text |Cite
|
Sign up to set email alerts
|

Body and peripersonal space representations in chronic stroke patients with upper limb motor deficits

Abstract: The continuous stream of multisensory information between the brain and the body during body–environment interactions is crucial to maintain the updated representation of the perceived dimensions of body parts (metric body representation) and the space around the body (the peripersonal space). Such flow of multisensory signals is often limited by upper limb sensorimotor deficits after stroke. This would suggest the presence of systematic distortions of metric body representation and peripersonal space in chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 89 publications
5
33
0
Order By: Relevance
“…However, further studies are needed to understand to what extent and under what conditions these two spaces may reveal similar behavioural displays. Furthermore, many studies have identified alterations of the representation of the space around the body in neurological [ 70 ], psychopathological [ 64 , 71 , 72 ] or autistic [ 19 ] patients. Therefore, in-depth knowledge of the mechanisms of sharing or segregation between action space and interpersonal social space may potentially suggest new ways to improve or rehabilitate the functions of representing the space around our bodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to understand to what extent and under what conditions these two spaces may reveal similar behavioural displays. Furthermore, many studies have identified alterations of the representation of the space around the body in neurological [ 70 ], psychopathological [ 64 , 71 , 72 ] or autistic [ 19 ] patients. Therefore, in-depth knowledge of the mechanisms of sharing or segregation between action space and interpersonal social space may potentially suggest new ways to improve or rehabilitate the functions of representing the space around our bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of BPs de cits after stroke has only been seldom investigated. Schwoebel and Coslett [6], Raimo and coauthors [17], Razmus [18] as well as Bassolino and co-authors [13] estimated altogether from 39.5-81% of stroke patients with a de cit in at least one component of BPs. This wide range is explained by the different experimental tasks used in each study, targeting different BPs, as well as by the different pro les of the patients included, varying by the phase of the disease (acute, sub-acute and/or chronic), the inclusion [18] or exclusion [6,17] of bilateral lesions, the selection of speci c lesion lateralisation (e.g.…”
Section: Prevalence Of Alterations In Bps After Strokementioning
confidence: 99%
“…allowing them to mimic the dynamic characteristics of natural movement (Krebs et al, 1998 ; Grange et al, 2001 ; Casadio et al, 2006 ). Movement-assistance robots would be particularly useful to improve the current assessment of BRs metrics in patients with sensorimotor deficits (Bassolino et al, 2022 ). For instance, motor impairments and spasticity (i.e., muscle stiffness, tightness, and rigidity) (Pantano et al, 1995 ; Sommerfeld et al, 2004 ) would prevent the use of active tasks in some patients with poststroke, thus limiting their assessment to static tasks (Longo and Haggard, 2012 ; Bassolino et al, 2015 ), or motor imagery skills (Shahvaroughi-Farahani et al, 2021 ).…”
Section: (Neuro)robotics To Assess Body Representationsmentioning
confidence: 99%
“…For instance, amputation or deafferentation is characterized by unpleasant phantom sensations and pain (Flor et al, 2006 ). In patients with chronic stroke with persistent sensorimotor deficits, the affected limb can be perceived as “foreign,” “ill,” and “like dead” (Bassolino et al, 2022 ; Crema et al, 2022 ).…”
Section: Distortion In Mental Body Representationsmentioning
confidence: 99%
See 1 more Smart Citation